Awareness and attitude of doctors and nurses at a crossmark teaching hospital to skin donation and banking (2014)
Introduction: This study sought to determine the awareness and attitude of doctors and nurses in a teaching hospital to skin donation and banking, and to identify needs for personnel educational programmes. Methods: A cross sectional survey on doctors and nurses was carried out using a 44-item questionnaire that included a Likert scale on attitudes. Predictors of favourable attitudes were determined. Results: Eighty (49.7%) doctors and 81 (50.3%) nurses participated in the study. Many participants, 126 (78.3%), knew that skin could be donated, but only 96 (59.6%) participants were aware of skin banking. The main source of information was during professional training (17.4%). Only 41 (25.5%) participants were willing to donate skin after death. Body disfigurement was the major reason (20.5%) against skin donation. Participants who were doctors, were aware of skin banking, and who were previous blood donors had higher attitudes scores (p < 0.001, p = 0.004, p = 0.007 respectively). Being a doctor and having heard of skin banking were predictors of favourable attitudes to skin donation and banking. Conclusion: Knowledge transfer during health professional training on the usefulness of banked skin in patients with major burns may lead to improved attitude of health professionals and acceptance of this modality of burn management.